Influencia de la denervación autonómica sobre la función pancreática en un modelo de síndrome metabólico experimental : desde el conocimiento fisiopatológico a la bioquímica clínica - Lopez Mingorance, Fabiana Norma (2015)
Metabolic Syndrome (MS), as defined by the ATP III, affects more than 20% of worldwide population. Insulin resistance (IR) is considered to be fundamental in it?s pathogenesis. An imbalance of the Autonomic Nervous System caused by environmental factors and lifestyle habits intervenes as well. The pancreas, trough the endocrine-exocrine axis, plays a role in the digestive process of all nutrients and regulates glucose homeostatic balance.\nWe analyzed, on MS patients, the relevance of the extended Glucose Oral Tolerance Test for diagnosis and treatment.\nThe exocrine alterations produced on IR, as a consequence of the disturbance on the endocrine-exocrine axis were studied by the Pancreolauryl Test.\nA study on a MS animal model put in evidence improvement in IR as a result of splanchnicectomy (interruption of the vagus-central-splanchnic circuit).\nIt is our postulation that splanchnicectomy shears through a modulatory brake of the hepatic cholinergic tone; enhances the release of the Hepatic Insulin Sensitizing Substance (HISS) a putative hormone that interacts synergically with insulin on skeletal muscle, heart and kidneys, increasing glucose disposal. It improves endocrine and exocrine pancreatic physiopathological response. It could be a helpful therapeutic tool for treatment of these pathologies in humans.\n